أثر أساليب التعلم وفعالية الذات الأكاديمية فى جودة الحياة لدى عينة من طلاب الجامعة - الأبيض، عادل عبدالمعطي (جامعة طنطا - كلية التربية, 2018)
تهدف الدراسة الحالية التحقق من اختلاف كل من أساليب التعلم (بصري- سمعي – حركي) وفعالية الذات الأكاديمية (منخفضة – مرتفعة) وكذلك أثر التفاعل بينهما في جودة الحياة وأبعادها (جودة الحياة الأسرية – جودة الحياة النفسية – جودة التعليم – جودة الحياة العامة)، وتكونت عينة الدراسة من (300) طالب من طلاب كلية التربية والآداب (المستوى الثاني)، جامعة الحدود الشمالية بعرعر – المملكة العربية السعودية، من تخصصات (الدراسات الإسلامية – اللغة العربية- التربية الخاصة- اللغات والترجمة)، وتم استخدام الأدوات الأتية: 1- مقياس أساليب التعلم من إعداد الباحث. 2- مقياس فعالية الذات الأكاديمية من إعداد الباحث. 3- مقياس جودة الحياة من إعداد الباحث، ومن خلال استخدام اختبار (ت) وتحليل التباين 3×2 توصلت الدراسة للنتائج الآتية: 1- عدم وجود فروق دالة إحصائياً بين أساليب التعلم (بصري – سمعي – حركي) في جودة الحياة بأبعادها (جودة الحياة الأسرية – جودة الحياة النفسية – جودة التعليم – جودة الحياة العامة) 2- وجود فروق دالة إحصائياً لصالح ذوي فعالية الذات الأكاديمية المرتفعة في جودة الحياة وأبعادها. 3- وجود أثر دال إحصائياً للتفاعل بين أساليب التعلم (بصري – سمعي – حركي) وفعالية الذات الأكاديمية (منخفضة – مرتفعة) في جودة الحياة وأبعادها.
The study investigates the relationship between the three styles of learning (visual, auditory, and kinesthetic) and academic self- efficacy (low or high) and the result of such, correlation on life quality and dimensions (i.e., quality of family life, quality of psychological life, quality of education, quality of public life). The study sample consisted of 300 freshmen from the departments of Islamic Studies, Arabic Language, Special Education and Languages and' Translation, Faculty of Education and, Arts, Northern Border University, Saudi Arabia. The following tools were used in conducting this study: learning styles scale, academic self-efficacy scale, quality of life scale, all of which were prepared by the researcher, in addition to the use of T test and analysis of variance 3x2. The study reached the following results: 1- There are no; statistically significant differences between learning styles (visual,- 'auditory - and kinesthetic) and life quality and dimensions above mentioned; 2- There are statistically significant differences in favor of high - academic self-efficacy in life quality and dimensions' and 3-There statistically significant correlation between learning styles .(visual, auditory, and kinesthetic) and academic self-efficacy (low, or high) in terms of life quality arid dimensions.
Keywords: أساليب التعلم -- الذات الأكاديمية -- جودة الحياة -- طلبة الجامعات